Total Aortic Arch Replacement after Thoracic Endovascular Aortic Repair Using Left Subclavian Arterial Perfusion - Sueda, Taijiro (Ann Thorac Cardiovasc Surg, 2018)
We present the case of an 86-year-old male with an aortic arch saccular aneurysm who underwent zone 1 thoracic endovascular aortic repair (TEVAR) with debranching from the right subclavian artery to the left carotid and left subclavian arteries. The patient developed a type Ia endoleak 1 month later. Postoperative contrast computed tomography (CT) showed a hematoma around the aneurysm, concerning for impending rupture. He thus underwent emergency endograft removal and replacement with a one-branched graft using selective cerebral perfusion via the left subclavian artery perfusion. The left subclavian artery was used for systemic and cerebral perfusion without need for cannulation of the cervical arteries. The patient was successfully discharged 6 months after surgery.